A comparative study of syndecan-1 expression in different odontogenic tumors - Shahroo Etemad-Moghadam; Mojgan Alaeddini (Elsevier, 2017)
Background: Expression of various cellular/molecular factors change during the course of tumor formation from odontogenic tissues of the tooth germ. Evaluation of these factors can help provide a better perception of the tumorigenesis and biologic behavior of odontogenic tumors (OTs). Syndecan-1 is a heparan sulfate proteoglycan which has not been extensively investigated in these lesions. The objective of the present study was to assess the immunohistochemical expression of CD138 in adenomatoid odontogenic tumor (AOT), ameloblastic fibroma (AF) and odontogenic myxoma (OM) and to compare it with ameloblastoma and keratocystic odontogenic tumor (KCOT). Method: A total of 58 OTs consisting of 7 AOTs, 5 OMs, 7 AFs, 29 KCOTs and 10 ameloblastomas were immunohistochemically stained with monoclonal antibody against syndecan-1 and the percentage and intensity of the immunostained cells was assessed. Kruskal-Wallis test followed by Bonferroni analysis was used for comparisons (P < 0.05). Results: Syndecan-1 was expressed in all samples except for OMs. Both percentage and intensity of syndecan-1 expression were statistically different among the studied OTs (P < 0.001). Pairwise comparisons showed significant difference only between OMs and each of the other tumors. Conclusion: Syndecan-1 may be involved in the pathogenesis of AOT, AF, KCOT and ameloblastoma. However, considering the different behaviors of these tumors along with their similar expression of syndecan-1, it seems that its effect on clinical aggressiveness is limited. The significance of negative immunoexpression of this protein in OM requires further investigation.